Making tough decisions well and badly framing, deciding, implementing, assessing - Woodside, Arch G. (Advances in business marketing & purchasing ;, 2016)
Where do brilliant executive wisdom and actions come from? Making Tough Decisions Well and Badly (MTDWB) assesses the literature that examines executives' conscious and non-conscious actions in decision making, implementation and assessment of outcomes. MTDWB includes anecdotal histories of good and bad decisions and the executives who made them. This volume uncovers the common threads in framing, forecasting, decision making and actions, looking at Steve Jobs, Martin Luther King, Jr, Senator Wayne Morris, Winston Churchill, Abraham Lincoln, Sam Walton, Mahatma Gandhi, and Bill Gates. Authors discuss how common threads could be useful for achieving superior competences. MTDWB assesses ten valuable decision making tools such as checklists and coaches; and tools to avoid such as use of product portfolio paradigms and use of fit-only regression analysis, that appear often in the popular business and academic literature on making tough decisions. MTDWB closes with ten recommendations for those responsible for making tough decisions.